2011
DOI: 10.1371/journal.pone.0021942
|View full text |Cite
|
Sign up to set email alerts
|

Influenza H5 Hemagglutinin DNA Primes the Antibody Response Elicited by the Live Attenuated Influenza A/Vietnam/1203/2004 Vaccine in Ferrets

Abstract: Priming immunization plays a key role in protecting individuals or populations to influenza viruses that are novel to humans. To identify the most promising vaccine priming strategy, we have evaluated different prime-boost regimens using inactivated, DNA and live attenuated vaccines in ferrets. Live attenuated influenza A/Vietnam/1203/2004 (H5N1) candidate vaccine (LAIV, VN04 ca) primed ferrets efficiently while inactivated H5N1 vaccine could not prime the immune response in seronegative ferrets unless an adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…Subsequent infection or immunization with a variant strain would likely be an effective route to generate broadly reactive anti-H5 antibodies. Such strategies are known to be effective within influenza subtypes (25,48,49). Our structural understanding of H5.3 supports the hypothesis that repeated challenge through immunization or infection is an effective strategy to enhance universal binding determinants, such as a CDRH3 loop that effectively binds conserved features of the RBS, similar to the natural receptor, while minimizing strainspecific interactions.…”
Section: Resultssupporting
confidence: 67%
“…Subsequent infection or immunization with a variant strain would likely be an effective route to generate broadly reactive anti-H5 antibodies. Such strategies are known to be effective within influenza subtypes (25,48,49). Our structural understanding of H5.3 supports the hypothesis that repeated challenge through immunization or infection is an effective strategy to enhance universal binding determinants, such as a CDRH3 loop that effectively binds conserved features of the RBS, similar to the natural receptor, while minimizing strainspecific interactions.…”
Section: Resultssupporting
confidence: 67%
“…With the current controversy surrounding the use of ferrets in influenza studies, it is important to remember that the reason for using ferrets extends far beyond that of providing a model for H5N1 transmission, as many investigators have shown ferrets to be a superlative platform for testing and developing influenza therapeutics including the investigation of influenza vaccines [26][27][28][29][30]. Importantly, when infected with respiratory viruses, ferrets display many of the symptoms and pathological features seen in infected humans [31][32][33] .…”
mentioning
confidence: 99%
“…The absence of anti-HA antibodies in such DNA-vaccinated groups was not surprising because previous dose-response studies have demonstrated variability in induction of HI antibodies, which play a major role in protection against avian influenza (Jiang et al, 2007). Moreover, poor humoral response has been previously reported with a homologous DNA-DNA prime-boost vaccination strategy (Suguitan et al, 2011). It is worth noting that in the present study, the absence of HI titers was directly related to the lowering of protective efficacy, in contrast to previous studies that showed protection in chickens despite the lack of any detectable anti-HA antibody titer (Kodihalli et al, 1997;Jiang et al, 2007).…”
Section: Discussionmentioning
confidence: 91%
“…Enhancement could be attributed to the induction of cell-mediated immune response as DNA vaccines are potent mobilizers of cellular immune response (Donnelly et al, 1997;Khan, 2013) via direct transfection of antigen presenting cells and/or cross priming (Iurescia et al, 2014). Earlier studies have shown that priming with HA-DNA is as effective as immunization with live attenuated influenza vaccine (LAIV) or with inactivated adjuvanted influenza vaccine (Suguitan et al, 2011). Results of the present study demonstrate that a prime-boost regimen using pcDNA3.1D/HA1 purified recombinant plasmid with the inactivated H5N2 vaccine is more immunogenic than the use of either pcDNA3.1D/HA1 purified recombinant plasmid or inactivated H5N2 vaccine alone.…”
Section: Discussionmentioning
confidence: 99%